Odpowiedzi

2009-11-17T17:01:41+01:00
-8+(-5)-(-7)+(-13)-(-10)-6= -8 - 5 + 7 - 13 + 10 - 6 = - 15

24-(-30)+(-62)-(-18)+(-41)-(-70)= 24 + 30 - 62 + 18 - 41 + 70 =39

-[-(-12)+(-5)]-[-(-17)-(-3)]= -[-(-12) -5]-[-(-17)+3] = -[12 -5]- [17+3]= - 7 - 20 = -27
3 3 3
2009-11-17T17:02:02+01:00
-8+(-5)-(-7)+(-13)-(-10)-6= - 8 - 5 + 7 - 13 + 10 - 6 = - 15
24-(-30)+(-62)-(-18)+(-41)-(-70)= 24 + 30 - 62 + 18 - 41 + 70 = 39
-[-(-12)+(-5)]-[-(-17)-(-3)]= - [12 - 5] - [17 +3 ] = -12 + 5 -17 - 3 = - 27

;)
1 2 1
2009-11-17T17:03:23+01:00
-8-5+7-13+10-6 = -15
24+30-62+18-41+70 = 39
-7-20 = -27
3 1 3